Two-phase flow-induced vibration fatigue damage of tube bundles with clearance restriction. (1st March 2022) - Lai, Jiang; Yang, Shihao; Lu, Lingling; Tan, Tiancai; Sun, Lei
Highlights: A mathematical model of tube bundles with clearance restriction was developed. Flow-induced vibration fatigue damages of the tubes were estimated based on S - N curves. Effects of flow pitch velocity and void fraction on fatigue damage were discussed. Abstract: Flow-induced vibration of the tube bundles in two-phase flow involves complicated interactions between the fluids and structures. Although a substantial number of studies have been devoted to investigating the flow-induced vibration and fluidelastic instability of the tube bundles subjected to two-phase cross-flow, the fatigue damage features of the tubes are not fully understood. In this paper, considering the effects of the turbulence random forces and the fluidelastic forces, a mathematical model of the tube bundles subjected to two-phase flow and the clearance restriction was developed. The vibration responses of the tube bundles within five void fraction conditions were calculated. The flow-induced vibration fatigue damages of the tubes were estimated based on S - N curves. The effects of the clearance restriction, the flow pitch velocity, and the void fraction of the two-phase flow on the fatigue damage were discussed. The numerical results demonstrate that the void fraction and flow pitch velocity of the two-phase flow have a significant influence on the fatigue damage of the tube bundles. And, the clearance restriction can change the location of the maximum fatigue damage.